Sociodemographic and psychological characteristics of school shooters in the United States: a systematic review of the literature - Minelli, Michela; Zappalà, Angelo; Vayr, Silvia; Santtila, Pekka (Frontiers in Psychiatry, 2026)
BackgroundSchool shootings represent a complex and critical phenomenon observed worldwide, though their frequency is particularly high in the United States compared to other developed countries. A systematic examination of the socio-demographic and psychological characteristics of school shooters is essential for identifying potential recurring patterns and advancing scholarly understanding of the phenomenon. Nonetheless, the current body of evidence remains fragmented and inconsistent.MethodsA systematic literature search was conducted across PubMed, PsycINFO, and Web of Science databases covering publications from 1900 to 2024. From an initial pool of 1,862 publications, 13 studies meeting inclusion criteria were selected for analysis. The review specifically focused on socio-demographic, psychological, and behavioral characteristics of school shooters, including age, gender, family background, social experiences, mental health, and risk behaviors.ResultsThe findings indicated that approximately 75% of the characteristics we aimed to analyze were not available in the reviewed literature. Despite these data limitations, some recurrent features emerged, such as social isolation, traumatic experiences (e.g., bullying, dysfunctional families), and problematic psychological traits (e.g., depression, narcissism, lack of empathy). Rather than revealing a single perpetrator typology, the evidence suggests the existence of multiple heterogeneous patterns shaped by individual differences and diverse contributing factors.DiscussionThe scarcity and fragmentation of data are linked to methodological heterogeneity and the lack of standardized protocols for data collection and analysis. Future research should prioritize the development of uniform methodologies to improve data quality and comparability. This would facilitate a deeper understanding of the phenomenon and strengthen preventive strategies. The review underscores the urgency of overcoming current research dispersion to identify meaningful patterns and dynamics.